2016
DOI: 10.1002/chem.201600630
|View full text |Cite
|
Sign up to set email alerts
|

Triazine‐Carbon Nanotubes: New Platforms for the Design of Flavin Receptors

Abstract: The synthesis of functionalised carbon nanotubes as receptors for riboflavin (RBF) is reported. Carbon nanotubes, both single-walled and multi-walled, have been functionalised with 1,3,5-triazines and p-tolyl chains by aryl radical addition under microwave irradiation and the derivatives have been fully characterised by using a range of techniques. The interactions between riboflavin and the hybrids were analysed by using fluorescence and UV/Vis spectroscopic techniques. The results show that the attached func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…XPS analysis was performed on pristine HSAG and on HSAG-TMP equimolar adducts obtained at 80 °C, 130 °C and 180 °C. It is widely acknowledged that XPS studies on functionalized hybrid materials are very helpful to elucidate the structure of the adducts [65,66,67]. Indeed, XPS analyzes the elemental composition of the samples as well as the types of chemical bonds, providing relevant information.…”
Section: Resultsmentioning
confidence: 99%
“…XPS analysis was performed on pristine HSAG and on HSAG-TMP equimolar adducts obtained at 80 °C, 130 °C and 180 °C. It is widely acknowledged that XPS studies on functionalized hybrid materials are very helpful to elucidate the structure of the adducts [65,66,67]. Indeed, XPS analyzes the elemental composition of the samples as well as the types of chemical bonds, providing relevant information.…”
Section: Resultsmentioning
confidence: 99%
“…32 The deprotection of the Boc group, present in the modified α-amino acid used, allows to verify the presence of free amino groups in the functionalized material (15) utilizing the Kaiser test. To localize the functional groups on the graphene layers, gold nanorods (AuNRs) were used as contrast marker agents exploiting their interaction with amines (16). The study of this hybrid by transmission electron microscopy (TEM) showed the presence of AuNRs distributed uniformly all over the graphene layers, corroborating the hypothesis that the 1,3-dipolar cycloaddition reaction occurs also in the central C-C bonds of FLG.…”
Section: Synthetic Pathways For Graphene Functionalization With Amino Groupsmentioning
confidence: 68%
“…15 The nitrogen lone pair allows amines to have supramolecular interactions, forming hydrogen and halogen bonds: this property is convenient in the field of sensing and catalysis. 16,17 Amino groups can undergo several chemical transformations due to their nucleophilic nature. This feature can be exploited for reactions with various electrophilic moieties, including aldehydes, acyl halides, and iso(thio)cyanates.…”
Section: Importance Of Amino Groups To Convey New Properties To Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many groups of starting compounds used for the functionalization of nanotubes and nanofibers [1][2][3][4][5][6][7], including those from the triazide family. In this paper, we investigate the physical and photochemical properties of one of the representatives of this familytriazido-s-triazine.…”
Section: Introductionmentioning
confidence: 99%